Quality of Life in Women with Gestational Diabetes Mellitus: A Systematic Review. (23rd February 2017) - Marchetti, Daniela; Carrozzino, Danilo; Fraticelli, Federica; Fulcheri, Mario; Vitacolonna, Ester
Abstract : Background and Objective . Diagnosis of Gestational Diabetes Mellitus (GDM) could significantly increase the likelihood of health problems concerning both potential risks for the mother, fetus, and child's development and negative effects on maternal mental health above all in terms of a diminished Quality of Life (QoL). The current systematic review study is aimed at further contributing to an advancement of knowledge about the clinical link between GDM and QoL. Methods . According to PRISMA guidelines, PubMed, Web of Science, Scopus, and Cochrane databases were searched for studies aimed at evaluating and/or improving levels of QoL in women diagnosed with GDM. Results . Fifteen research studies were identified and qualitatively analyzed by summarizing results according to the following two topics: GDM and QoL and interventions on QoL in patients with GDM. Studies showed that, in women with GDM, QoL is significantly worse in both the short term and long term. However, improvements on QoL can be achieved through different intervention programs by enhancing positive diabetes-related self-management behaviors. Conclusion . Future studies are strongly recommended to further examine the impact of integrative programs, including telemedicine and educational interventions, on QoL of GDM patients by promoting their illness acceptance and healthy lifestyle behaviors.